2010
DOI: 10.1371/annotation/9e6e8b98-cc08-47be-9ab1-3f1928e12fed
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Ultra-Fast Analysis of Plasma and Intracellular Levels of HIV Protease Inhibitors in Children: A Clinical Application of MALDI Mass Spectrometry

Abstract: HIV protease inhibitors must penetrate into cells to exert their action. Differences in the intracellular pharmacokinetics of these drugs may explain why some patients fail on therapy or suffer from drug toxicity. Yet, there is no information available on the intracellular levels of HIV protease inhibitors in HIV infected children, which is in part due to the large amount of sample that is normally required to measure the intracellular concentrations of these drugs. Therefore, we developed an ultra-fast and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Moreover, DI-MS methods offer a considerable advantage of rapidity and low-sample input for drug quantification. DI-MS methods have extensively been used for the quantification of drugs in fluids [5][6][7][8][9][10][11], recently supported by full method validation [11]. In addition to the advantage of rapidity, DI-MS of drugs in tissue sections preserves histological contexts and can be performed at different dimensional scales, from profiling (when regions of interest are measured) [1,2,12] to imaging (when a complete drug mapping is necessary) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DI-MS methods offer a considerable advantage of rapidity and low-sample input for drug quantification. DI-MS methods have extensively been used for the quantification of drugs in fluids [5][6][7][8][9][10][11], recently supported by full method validation [11]. In addition to the advantage of rapidity, DI-MS of drugs in tissue sections preserves histological contexts and can be performed at different dimensional scales, from profiling (when regions of interest are measured) [1,2,12] to imaging (when a complete drug mapping is necessary) .…”
Section: Introductionmentioning
confidence: 99%
“…Desorption/ionization (DI) methods offer a range of outstanding advantages for drug quantification in biological matrices [ 1 , 2 ], using assays which can be validated according to regulatory guidelines [ 1 ]. These advantages include the rapidity of sample preparation and analysis from any biological matrix, including fluids [ 3 , 4 , 5 , 6 , 7 , 8 ], and the ability to quantify drugs in their histological context when tissue sections are used [ 1 , 9 , 10 ]. Our group has previously shown that the surface properties of the biological matrix in desorption electrospray ionization (DESI) [ 11 ] or the matrix crystallization effects in matrix-assisted laser desorption/ionization (MALDI) [ 2 , 12 ] can strongly affect signal stability compared to electrospray ionization (ESI).…”
Section: Introductionmentioning
confidence: 99%